2021
DOI: 10.1093/nsr/nwab006
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 reinfection in the presence of neutralizing antibodies

Abstract: In the face of the coronavirus disease 2019 (COVID-19), strong and long-lasting immunity is required to protect the host from secondary infections. Recent studies revealed potential inadequacy of antibodies against SARS-CoV-2 in some convalescent patients, raising serious concerns about COVID-19 reinfection. Here, from 273 COVID-19 patients, we identified six reinfections based on clinical, phylogenetic, virological, serological, and epidemiological data. During the second episode, we observed re-em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
7
23
0
1
Order By: Relevance
“…However, it was not sterizing immunity, and the virus still moderately replicated in nasal turbinates of prior infected hamsters, indicating that prior infected hamsters can be artificially re-infected after a short recovery period, even with a high level of neutralization antibodies. The conclusion is consistent with recent reports showing that recovered COVID-19 patients were re-infected in the presence of neutralizing antibodies 24,25 . A large study of a recovered cohort of 175 COVID-19 patients revealed that 6% of COVID-19 patients did not show any antibody response at all, and about 30% COVID-19 patients showed very low neutralizing antibodies 26 .…”
Section: Discussionsupporting
confidence: 93%
“…However, it was not sterizing immunity, and the virus still moderately replicated in nasal turbinates of prior infected hamsters, indicating that prior infected hamsters can be artificially re-infected after a short recovery period, even with a high level of neutralization antibodies. The conclusion is consistent with recent reports showing that recovered COVID-19 patients were re-infected in the presence of neutralizing antibodies 24,25 . A large study of a recovered cohort of 175 COVID-19 patients revealed that 6% of COVID-19 patients did not show any antibody response at all, and about 30% COVID-19 patients showed very low neutralizing antibodies 26 .…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we first showed that previously infected Syrian hamsters can be naturally reinfected by direct contact or the airborne route in an intense reexposure setting, but with lower viral titers in upper respiratory tract. This conclusion is consistent with recent reports showing that recovered COVID-19 patients were reinfected in the presence of neutralizing antibodies ( Selhorst et al, 2020 ; Zhang et al, 2021 ), and low levels of subgenomic RNA was detected in the nasal swabs of previously infected rhesus macaques when rechallenge ( Chandrashekar et al, 2020 ). Different from our results, several recent studies reported that prior infection in COVID-19 patients was highly protective against SARS-CoV-2 reinfection, with protective efficiency from 81.4 to 95.2% ( Abu-Raddad et al, 2020 , 2021b ; Rennert and McMahan, 2021 ; Sheehan et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…SARS-CoV-2 transmission study between prior infected rhesus macaques and the naïve animals was not found. Several human COVID-19 reinfection cases have been reported 1 year before ( To et al, 2020 ; Van Elslande et al, 2020 ), even in the presence of neutralizing antibodies ( Selhorst et al, 2020 ; Zhang et al, 2021 ). Hence, the recovered COVID-19 patients still need to follow public health measures and keep on personal protection.…”
Section: Introductionmentioning
confidence: 99%
“…The conducted analysis confirms the hypothesis that the likelihood of experiencing SARS-CoV-2 symptomatic infection is greatly reduced in individuals already infected in the previous 8-10 months 11 . In line with what observed elsewhere [7][8][9]13,14 , our findings suggest that the relative risk of symptomatic infection for individuals who previously tested positive to IgG antibodies compared to seronegative subjects is less than 6%.…”
Section: Mainsupporting
confidence: 92%